Budaya Populer Dalam Pembuatan Video Klip (Studi Kasus Pada Video Klip ‘Merakit’ Oleh Yura Yunita) - Jenny Ratna Sari; Roswita Oktavianti (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
Popular culture is dominated by the production and consumption of material goods whose creation is driven with the motive of profit.Video clips are also used to gain profit or profit for their creators.The study raised how popular culture is in the making of video clips.This research is a qualitative study with case study methods. The researcher conducted a case study of the video clip titled